2002
DOI: 10.1177/0273475302241006
|View full text |Cite
|
Sign up to set email alerts
|

A Professional School Approach to Marketing Education

Abstract: With many business schools paying lip service to the concept of professional training, this article attempts to provide some direction for moving from an academic or liberal-arts-oriented marketing department to a professional marketing program. The transformation to a professional school perspective can be facilitated by marketing programs examining other professional schools to identify how these programs differ from their current programs. A professional school approach to marketing education meets the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 44 publications
1
72
0
1
Order By: Relevance
“…Specifically, analytical skills are highly valued in business education as they represent critical thinking and problem-solving ability (Hunton, 2002;Schibrowsky, Peltier, & Boyt, 2002). Thus, the learned importance of analytical skills transfers into the business world when former students themselves become evaluators.…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, analytical skills are highly valued in business education as they represent critical thinking and problem-solving ability (Hunton, 2002;Schibrowsky, Peltier, & Boyt, 2002). Thus, the learned importance of analytical skills transfers into the business world when former students themselves become evaluators.…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 99%
“…Thus, the learned importance of analytical skills transfers into the business world when former students themselves become evaluators. Such skills also allow for better reactions to dynamic situations such as integration, which often requires meshing of different technical systems and collaborative efforts among unfamiliar personnel (Osegowitsch, 2001;Schibrowsky et al, 2002;Strang & Meyer, 1993).…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 99%
“…They are convinced that the shift towards exactly the kind of research recommended in the reports caused the gap. They and others (Beer, 2001;Ivancevich, Duening, & Lidwell, 2005;Pfeffer & Fong, 2002;Schibrowsky, Peltier, & Boyt, 2002;Trank & Rynes, 2003) claim that business shares more characteristics with professions like medicine and law than it does with natural sciences, and that research in the field of management studies should therefore adopt the alternative model of applied research.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Young, Klemz and Murphy (2003, p.132) found that 'Empirical evidence supports that business students prefer pedagogies that are active and concrete', while Hunt, Eagle and Kitchen (2004) found that business students showed the greatest preference for traditional (didactic) methods, and the lowest preference for student-based methods (student presentations and group work). There is no doubt that many business and marketing educators advocate greater use of interactive, experiential learning methods (Cunningham 1999;Daly 2001;Schibrowsky, Peltier & Boyt 2002;Smith & Van Doren 2004). Case studies occupy a potentially valuable position in the portfolio of pedagogic methods, since the approach is familiar to business students, and yet offers the lecturer various degrees of student involvement, from traditional teacher-centred classroom discussions to 'live cases' which involve student teams in extensive interactions inside and outside the classroom (Kennedy, Lawton & Walker 2001).…”
Section: T Th He E C Ca As Se E S St Tu Ud Dy Y M Me Et Th Ho Od Dmentioning
confidence: 99%